2010
DOI: 10.4028/www.scientific.net/kem.434-435.783
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High Thermal Conductivity β-Si<sub>3</sub>N<sub>4</sub> Ceramics at Relatively Low Temperature Using MgSiN<sub>2</sub> as Additives

Abstract: Silicon nitride ceramics with MgSiN2 as additives were sintered by hot pressing at 1600° ~ 1750 °C for 1-12 h under uniaxial pressure of 20 MPa. The specimens were characterized by x-ray diffraction, scanning electron microscopy, transmission electron microscopy and photothermal deflection spectroscopy. After sintered at 1750°C for 1 h, the thermal conductivity of the material was 90 W·m-1·K-1. The thermal conductivity could remarkably increase to 120 W·m-1·K-1 by prolonging the dwell time from 1 h to 12 h. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For instance, the thermal conductivity of Si 3 N 4 ceramics can be improved by the use of MgSiN 2 instead of MgO. With the addition of nitride additives the increased N/O ratio in the grain boundary glassy phase was found, thus the grain growth was promoted and the grain lattice was purified . Recently, Li substituted Y 2 O 3 by Y 2 Si 4 N 6 C and demonstrated that Y 2 Si 4 N 6 C reacted with inherent SiO 2 to form liquid phase Y 2 Si 3 O 3 N 4 and volatile CO(g) resulting in a decrease of oxygen and an increase of N/O ratio in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the thermal conductivity of Si 3 N 4 ceramics can be improved by the use of MgSiN 2 instead of MgO. With the addition of nitride additives the increased N/O ratio in the grain boundary glassy phase was found, thus the grain growth was promoted and the grain lattice was purified . Recently, Li substituted Y 2 O 3 by Y 2 Si 4 N 6 C and demonstrated that Y 2 Si 4 N 6 C reacted with inherent SiO 2 to form liquid phase Y 2 Si 3 O 3 N 4 and volatile CO(g) resulting in a decrease of oxygen and an increase of N/O ratio in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of nitride additives the increased N/O ratio in the grain boundary glassy phase was found, thus the grain growth was promoted and the grain lattice was purified. 18,19,29 Recently, Li substituted Y 2 O 3 by Y 2 Si 4 N 6 C and demonstrated that Y 2 Si 4 N 6 C reacted with inherent SiO 2 to form liquid phase Y 2 Si 3 O 3 N 4 and volatile CO(g) resulting in a decrease of oxygen and an increase of N/O ratio in the liquid phase. The densified Si 3 N 4 ceramics exhibiting 120 W·(m·K) −1 with enlarged grains, reduced lattice oxygen content, increased grains contiguity and more crystallized intergranular phase were fabricated.…”
mentioning
confidence: 99%
“…The densified Si 3 N 4 ceramics possessing 120 W m −1 K −1 with reduced lattice oxygen content, enhanced grains contiguity, and decreased glassy phase were fabricated 21 . Besides, many studies have demonstrated that the substitution of MgO by MgSiN 2 induced a nitrogen‐rich liquid phase, which would inhibit the oxygen dissolution, thus benefit the thermal conductivity of Si 3 N 4 ceramics 16,22,23 . Apart from fluorides and nitrides, our previous work demonstrated that ZrSi 2 eliminated inherent SiO 2 and in situ generated ZrO 2 and β‐Si 3 N 4 grain seeds resulting in a decrease in oxygen and an increase in N/O ratio in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…21 Besides, many studies have demonstrated that the substitution of MgO by MgSiN 2 induced a nitrogen-rich liquid phase, which would inhibit the oxygen dissolution, thus benefit the thermal conductivity of Si 3 N 4 ceramics. 16,22,23 Apart from fluorides and nitrides, our previous work demonstrated that ZrSi 2 eliminated inherent SiO 2 and in situ generated ZrO 2 and β-Si 3 N 4 grain seeds resulting in a decrease in oxygen and an increase in N/O ratio in the liquid phase. Benefit from enlarged purified grains, reduced oxygen dissolution, increased grains contiguity, and the densified Si 3 N 4 ceramics with a thermal conductivity of 113 W m −1 K −1 were achieved.…”
Section: Introductionmentioning
confidence: 99%